Pengaruh Persepsi Siswa atas Fasilitas Belajar dan Kompetensi Guru terhadap Keterampilan Membaca Bahasa Inggris - Surasni Surasni; Achmad Sumali (Neolectura, 2022)
The purpose of this study is to determine students' reading skills in English lessons which are influenced by students' perceptions of existing learning facilities and teacher competencies. The influence of students' perceptions of learning facilities with Teacher competencies together can improve students' Reading Skills. This research is also to determine the influence of students' perceptions of Learning Facilities and to determine the influence of Vocabulary Mastery on Reading Skills. The research method used is Experimental research. The study sample consisted of 30 students of English Class A as an experimental class for Audio Learning Styles and Visual Learning Styles, while English Class B consisted of 30 students as a Control class for High Vocabulary and Low Vocabulary. Data collection was obtained by conducting learning outcome tests, data analysis was obtained by applying descriptive analysis and statistical analysis with 2-way Anova.